Kraft Paper Insulation’s Life Assessment and Effects of Oxygen and Moisture to Paper Insulation’s Deterioration Rate - Sutan Chairul, Imran; Ab Ghani, Sharin; Ahmad Khiar, Mohd Shahril; Md Thayoob , Yasmin Hanum; Yang Ghazali, Young Zaidey (2012)
Examples of electrical insulations for transformer are mineral oil and cellulose based paper. The said insulations degraded as transformers performed their work, while the most critical component of the transformer insulation system is the paper insulation. It is not easily replaced as compared to oil where it is easily reconditioned in-order to remove water and contaminants. Studies on paper insulation showed that temperature, oxygen and moisture contents contributed to its degradation. Moisture and Furan were produced from these deterioration processes. The paper is focused on the effect of oxygen and moisture contents to deterioration rate of Kraft paper insulation and end-of-life analysis using 2 Furaldehyde (2FAL). Level of temperature, oxygen, moisture contents and 2FAL were obtained from in-service distribution power transformers. Assessments were then carried out on these collected data to determine the effect of oxygen and moisture contents to 2FAL formation. Categorizations were then carried out on 2FAL data for end-of-life analysis using Weibull as a life data analysis. This study shows that moisture give more implication to paper insulation degradation rate compared to oxygen and the end-of-life in years derived from Weibull probability function can be used to estimate the life of paper insulation.